Approach to illicit evidence in the labour process: Video surveillance as a form of labour control - Soto Zevallos, María Stephany (2020)
The aim of this paper is to highlight the ductility of the legislative limit of the employer’s supervisory power. This is favoured by the use of abstract terms such as «reasonable and necessary». These terms are left to the employer to define and justify the application of labour inspection measures, such as video surveillance. The referred ductility allows the obtaining of evidence with violation of the fundamental right of the worker to the protection of personal data related to his dignity. Frequently, the evidence is relevant —especially when it relates to the imposition of disciplinary measures— and it is admitted into labour proceedings without any additional filter. The latter violates due process, because it allows the entry of illicit evidence; consequently, there is a transgression that also impacts on the inefficient use of available resources, as well as the incorporation of contaminated information into the process.